MECHANISM OF MONOCARPIC SENE SCENCE OF TRICHOSANTH ES DIOICA Roxn (CucuRBITACEAE): Short Communication (Biological Sciences - PJSIR, 2002)
Most of the Cucurbitaceous plants are hermaphrodite. In this respect Trichosanthes dioica Roxb (Cucurbitaceae), common name parval seems to be an ideal for studying the role of fruits as well as :flowers as both fruits and flowers are present in a single or in different plant system and may contribute for the manifestation of senescence syndrome. This is be cause in Trichosanthes 3 types of plants (male, female and hermaphrodite plants) developed in the same field naturally even under non-competitive condition. The present paper aims at seperating the role of male flowers and female flowers in relation to their combined affect (hermaphrodite plants) so as to prove the effect of senescence signal during correlative senescence of such  plants.